Health-protective behavior during the pandemic: Does media exposure to COVID-19 information matter? - Amin, Kholidil; Mahameruaji, Jimi Narotama; Pranata, Allan Dwi; Madu, Augustine Uzoma; Nurizal, Hendri (Jurnal Kajian Komunikasi, 2023)
Background: The COVID-19 pandemic has prompted people to seek and get information on COVID-19 through the mass media or social media. It is expected to impact their beliefs, attitudes, and actions toward health-protective behavior. Purpose: This study aims to see how health-protective behavior amid a pandemic is predicted by exposure to COVID-19 information in the mass media and on social media. Methods: The current study advances the theory of planned behavior by surveying 413 persons cross-sectionally on Java Island, Indonesia. PLS-SEM was employed to assess measurement and structural models in order to answer the hypotheses. Results: The findings reveal that using mass media and social media to receive knowledge about COVID-19 strongly predicts intentions and behavior to apply preventive behavior, which is mediated by perceived behavioral control (PBC) and attitude. Conclusion: This research concludes that social media and mass media significantly positively influence three important aspects of forming behavioral intentions, and it also found that attitude, subjective norms, and PBC are important aspects of existing behavioral intention. Implications: This research also looks at the theoretical and practical ramifications. Theoretically, media use is related to the application of the TPB model. Practically, the government needs to optimize the mass media and social media use to reach the public with lots of valid, easy-to-understand COVID-19 information and generate positive optimism from the public.